Balancing Jealousy And Privacy In Islamic Marital Jurisprudence: Insights Through The Lens Of Maqasid Al-shariah - Nurul Syazwana Rosli; Nurul Aqilah Hishamuddin; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
This study explores the interplay between jealousy, privacy, and marital harmony through the lens of Islamic jurisprudence, guided by the higher objectives of Islamic law (Maqasid al-Shariah). Jealousy is recognised as a natural and potentially constructive emotion in intimate relationships, but its excessive forms, such as one spouse spying on the other, raise significant privacy concerns and undermine the sanctity of marriage. Using an in-depth fiqh analysis of classical legal rulings on spying (tajassus) versus permissible inquiry (tahassus), the study confirms that intrusive spousal surveillance is generally prohibited, as it erodes trust and marital stability. Nevertheless, allowances are acknowledged in extraordinary circumstances where discreet investigation might prevent greater harm or preserve the marriage, consistent with Maqasid al-Shariah’s family preservation. The findings further highlight the detrimental consequences of spying, including psychological distress, communication breakdown, and an increased risk of divorce. Based on these insights, the study proposes Islamic jurisprudence-based strategies to rebuild trust, enhance communication, regulate emotional responses, and employ Islamic family law mechanisms for conflict resolution. By integrating ethical and legal principles rooted in Maqasid al-Shariah, this research offers practical guidance to strengthen marital bonds and promote Islam’s overarching values of justice, dignity, and social harmony.